International Directory of Company Histories; Vol. 76 - Grant, Tina, editor 651952; Gale Group (Online service) 651863 (St. James Press, 2006)
Provides histories of companies that are a leading influence in a particular industry or geographic location. For students, job candidates, business executives, historians and investors.